PASAR UANG BERDASARKAN PRINSIP SYARIAH - Luqman Hakim (The Pontianak State Institute of Islamic Studies, 2014)
In the field of banking, money market is a means of interbank transactions that lack or excess liquidity. In the money market, the application still uses interest as a means of profit making. However, currently there is money market based on the principles of the Sharia, and it has got the National Shariah Board (DSN) fatwa legality No. 37 on the interbank money market with its syariah principles as a solution for both parties. However this fatwa still needs to be examined and re-evaluated to see if the fatwa really covers all the problems occurred in the interbank money market.